Revolutionizing Education: Enhancing Numeracy Skills with the Innovative Monster Math Game: Merevolusi Pendidikan: Meningkatkan Keterampilan Berhitung dengan Game Monster Math yang Inovatif - Pitanti, Anies Mey (Pedagogia : Jurnal Pendidikan, 2023)
The development of Information Communication and Technology (ICT) has an impact on the education. But teacher still use conventional methods. Therefore, this research aims to develop educational game media using the Construct 2 to improve the literacy numeracy skills of third grade elementary school students that are valid, practical, and effective. This development research refers to the ADDIE. The results of the development were applied to class III students at SD Negeri Janti for the 2022/2023 academic year. The development product is the Monster Math Game. The research instruments are validation sheets, questionnaires, and literacy numeration questions. The validity test was obtained from 3 experts, namely Curriculum Expert, Material Expert, and Media Expert. Results form Curriculum Expert at 87.5%, Material Expert at 86.4%, and Media Expert at 89.3%. So, it can be concluded that the Monster Math Game is very feasible to use to improve the literacy numeracy skills of Class III Elementary School. The results of the practicality test from educators were 89.3% and the practicality tests from students were 94.15%. From these results, it can be concluded that the Monster Math Game is very practical to use. The results of the effectiveness test through the t-test obtained the results of the sig value. (2-tailed) of 0.000 which means the sig. (2-tailed) < 0.05, so there is a significant difference between the results of the pre-test and post-test, it’s means that the Monster Math Game product is effective in improving the literacy numeracy skills of class III elementary school.